2016
DOI: 10.1186/s12933-016-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on carotid intima-media thickness in patients with type 2 diabetes and coronary artery disease. Influence of carotid plaques

Abstract: BackgroundCarotid intima-media thickness (cIMT) holds prognostic information for future cardiovascular disease and is associated with the extent of coronary atherosclerosis. We investigated the effect of exercise on cIMT progression in patients with both type 2 diabetes and coronary artery disease (CAD).MethodsPatients with type 2 diabetes and CAD (n = 137) were randomized to exercise training or standard follow-up. The 12 month exercise program contained 150 min weekly of combined aerobic and resistance train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 38 publications
(53 reference statements)
3
43
0
Order By: Relevance
“…Moreover, there is a quantitative relationship between HbA1c levels and plaque texture in ultrasonic images of atherosclerotic patients [49], and in those without identified carotid plaques, beneficial effect of exercise training on carotid IMT progression has been demonstrated [50]. On the other hand, these favorable effects have not been always seen [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a quantitative relationship between HbA1c levels and plaque texture in ultrasonic images of atherosclerotic patients [49], and in those without identified carotid plaques, beneficial effect of exercise training on carotid IMT progression has been demonstrated [50]. On the other hand, these favorable effects have not been always seen [51].…”
Section: Discussionmentioning
confidence: 99%
“…All studies were conducted in sedentary individuals. Eight studies recruited both male and female participants [28][29][30][31][32][33][34][35], three studies exclusively recruited male participants [36][37][38], and two studies recruited females exclusively [39,40]. Only 3 studies had a control group [28,35,38].…”
Section: Characteristics Of the Studies And Summary Of Outcome Measuresmentioning
confidence: 99%
“…RT on weight machines was used in one study with high intensity [31] and elastic resistance bands with low intensity were used in another study [39]; frequency of training was 3 days a week for 14 months and 5 days a week for 12 weeks, respectively. The usage of resources for combined training among the 11 studies was as follows: -7 studies used weight machines [28,32,33,[36][37][38]40] -2 free weights [29,30] -1 elastic resistance bands [34] -1 did not include information on the kind of exercise [35] The frequency of CT was most commonly 2 or 3 days per week and duration was between 4 weeks and 12 months.…”
Section: Characteristics Of the Studies And Summary Of Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Byrkjeland et al found no correlation between in LDLcholesterol and CIMT, inferring that increase in LDLcholesterol did not influence CIMT progression [12] . In contrast, Kota et al reported that glycemic parameters as FBG, and HbA1C collectively with lipid parameters were all significantly higher in diabetic patients with increased CIMT values [11] .…”
Section: Discussionmentioning
confidence: 94%